Dynamic transparency: An audit of Mexico's freedom of information act - Paul Lagunes; Oscar Pocasangre M. (Inter-American Development Bank (IDB), 2017)
Freedom of Information Acts (FOIAs) aim to provide a channeled exchange between citizens and public officials that, irrespective of the citizen's identity, results in the provision of timely, relevant, and often new information about policy. The authors of this paper evaluated Mexico's FOIA by submitting 307 information requests on behalf of an average male citizen to government entities in the years 2007, 2013, and 2015. In 2007, the authors also submitted the same requests to 87 comparable entities on behalf of a male citizen who signaled clout. For the most part, entities are not discriminating between regular and seemingly influential citizens. Entities are also answering more frequently and providing more information in 2015 compared to earlier years, but they are taking longer to answer, frequently charging fees, and often failing to provide quality information to questions they are legally bound to answer. Mexico's FOIA is a functional system demanding significant improvements.
Keywords: D73; 330; Transparency; Accountability; Freedom of Information Acts (FOIAs)